Nursing pharmacology made incredibly easy!
Nursing Pharmacology Made Incredibly Easy, 3rd Edition, provides the nursing student and practicing nurse with important information about how drugs act and interact in the treatment of disease. This essential pharmacology reference focuses on the mechanisms of drug action; details specific drugs by pharmacologic class; reviews the nursing process related to each drug category for all body systems, plus pain medications, anti-infective drugs, and cancer drugs; and highlights potentially dangerous interactions, including drug-herb interactions